Mediaesthetics of blank forms: the material basis of cultural nomadism in the era of panmediatization - Zagidullina, Marina (Przegląd Wschodnioeuropejski, 2018)
The article is devoted to the concept of the “empty form”. This concept is considered from philosophical, communicative, sociological, artistic and cultural points of view. The author follows Aristotle’s philosophy of hylomorphism and “eidos” and its transformation into the 20th century theory of “new materiality” with the “emptiness of the center” and “assemblage of things” concepts, in the modern linguistic approaches and in art and creative industries (i.e. painting, architecture, literature). The metaphor “frame without painting” (G. Zimmel) helps us understand the social potential of the “empty form” concept (as a functional stimulus and condition of perception). The modern communication situation, characterized by a panmediatization of all sides of societal life and a penetration of media in all forms of sociality, provides a number of conditions leading to an increase of the role of “empty forms” (including creativity based on “ready-to-use” empty forms considered as “vacuums waiting to be filled”). Panmediatization makes possible “the cultural nomadism” as a rambling from one empty form to another one. Panmediatization creates a “cultural nomadism” that consists of rambling from one empty form to another. One can see how the panmediatized communication field organizes this rambling: any “cultural nomad”, or rambler, is provided an opportunity to create new senses and new objects in the virtually endless and timeless space of this field. The technical aspect nature of this field generates the phenomenon of media aesthetics – the process of never-ending creative activity and consumption and evaluation of its results, where the aesthetic judgement is embodied in the technical procedures of the panmediatized communication field (i.e. “likes” or “sharing” of social media).